Effect of tempering time on the microstructure and stress rupture properties of P92 steel. (2021) - Maddi, Lakshmiprasad; Shivhare, Rishi; Kumar, Vijay; Goel, Manish; Ramesh, Mridula; Ballal, Atul
Abstract: P92 steels (9 Cr – 0.5 Mo – 1.8 W) are one of the candidate materials for Ultra Super Critical (USC) power plants. Since normalization of P92 results in the formation of martensitic microstructure, the steel is generally used in the normalized and tempered condition. In the present work, the material is subjected to normalization at 1060 °C and the effect of tempering time has been studied at constant tempering temperature of 780 °C. Decrease in dislocation density, increase in lath width, and precipitate size are the predominant microstructural changes. Short term (∼500 h) stress rupture tests are conducted at 600 °C temperature and structure – property correlation is attempted.